2004
DOI: 10.1023/b:brea.0000032984.56442.35
|View full text |Cite
|
Sign up to set email alerts
|

Is Stereotactic Large-Core Needle Biopsy Beneficial Prior to Surgical Treatment in BI-RADS 5 Lesions?

Abstract: SummaryIntroduction. Due to screening mammography, more nonpalpable mammographic lesions warrant histological evaluation. Stereotactic large-core needle biopsy (SLCNB) has been shown to be as effective in diagnosing these lesions as diagnostic surgical excision, and has become the preferred diagnostic procedure for most mammographic lesions. Since radiologically malignant BI-RADS 5 lesions are almost always carcinoma, some centers advocate prompt diagnostic surgical excision for these lesions instead of SLCNB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
6
0
6
Order By: Relevance
“…The 161 patients had a preoperative biopsy 142 of them had core needle biopsy. But we could not analyze the rate of underestimation of core biopsy described in the literature, because we excluded all patients with invasive carcinoma (1,12,16). But we can underestimate in situ or microinvasive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The 161 patients had a preoperative biopsy 142 of them had core needle biopsy. But we could not analyze the rate of underestimation of core biopsy described in the literature, because we excluded all patients with invasive carcinoma (1,12,16). But we can underestimate in situ or microinvasive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A Breast Imaging Reporting and Data System (BI-RADS) lexicon was developed by the American College of Radiology to standardize mammographic findings and assign a level of cancer suspicion to each finding, ranging from 1 (normal) to 5 (highly suggestive of malignancy). For BI-RADS 5 lesions presenting as mammographic densities alone, Hoorntje et al propose to consider surgical excision with sentinel node biopsy to be the first diagnostic and therapeutic procedure, whereas imaging-guided core-needle biopsy is preferred in all other cases [22]. The increase in preoperative breast cancer diagnosis through 1995-2004 reflects the increasing use of percutaneous biopsy and the implementation of biopsy techniques such as CB and SCNB.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods of percutaneous biopsy of DCIS, which have become the standard of care for breast cancer diagnosis, possess an inherent sampling error that can underestimate the presence of invasive disease [17][18][19][20]. Compared with initial core-needle biopsy results, invasive disease is present in up to 35% of cases on final excisional pathology [17][18][19][20]. Dominguez et al [21] recently reported that 11% of patients undergoing mastectomy for DCIS were found to have invasive cancer on final pathology.…”
Section: Discussionmentioning
confidence: 99%